Understanding food consumption lifecycles using wearable cameras. Issue 7 (October 2015) - Ng, Kher; Shipp, Victoria; Mortier, Richard; Benford, Steve; Flintham, Martin; Rodden, Tom
Abstract Application of design in HCI is a common approach to engendering behavioural change to address important challenges such as sustainability. Encouraging such change requires an understanding of current motivations and behaviours in the domain in question. In this paper, we describe use of wearable cameras to study motivations and behaviours around food consumption by focusing on two contrasting cultures, Malaysia and the UK. Our findings highlight the potential of wearable cameras to enhance knowledge of food consumption practices and identify where and how some digital interventions might be appropriate to change food behaviour. This includes appealing to people's motivations behind food consumption and capitalising on existing practices such as gifting of food and social meals. We propose a food consumption lifecycle as a framework to understand and design human–food interaction. The use of wearable cameras enabled us to capture a high-level overview of spatially distributed food-related practices and understand food behaviours in greater depth.